Pengaruh Gaya Kepemimpinan Situasional Terhadap Kinerja Pegawai dalam Dunia Penerbangan: Aisyah Rahmayani, Rany Adiliawijaya Putriekapuja - Rahmayan, Aisyah; Rany Adiliawijaya, Putriekapuja (Jurnal Teknologi dan Manajemen Sistem Industri, 2024)
This study explores the use of situational leadership in the aviation industry through a Systematic Literature Review (SLR). Out of 16 journals identified, 5 met the quality criteria. The results indicate that situational leadership greatly improves employee performance, particularly when supported by digital technologies that enable effective communication and real-time performance tracking. Adapting leadership styles to suit individual employee needs and dynamic work environments is critical for boosting productivity and operational efficiency. Additionally, situational leadership shows potential in enhancing safety compliance and reducing incidents compared to traditional leadership, especially when backed by strong organizational commitment and a supportive workplace culture. The study concludes that situational leadership, when properly implemented and integrated with technology, offers an effective approach to managing human resources in the aviation sector.